Two-stage Hall-Petch relationship in Cu with recrystallized structure. (1st July 2020) - Tian, Y.Z.; Ren, Y.P.; Gao, S.; Zheng, R.X.; Wang, J.H.; Pan, H.C.; Zhang, Z.F.; Tsuji, N.; Qin, G.W.
Abstract: Although Cu was studied extensively, the Hall-Petch relationship was mainly reported in the coarse-grained regime. In this work, fully recrystallized Cu specimens with a wide grain size regime of 0.51–14.93 μm manifest a two-stage Hall-Petch relationship. There is a critical grain size of 3 μm that divides stages I and II where the Hall-Petch slope k value are quite different. The stage II is supposed to be validified down to 100 nm at least by comparing with a Cu-Ag alloy. The critical grain size varies in different materials systems, and the underline mechanisms are discussed based on the dislocation glide modes.